Esophagitis Dissecans Superficialis in a Frail Older Patient: Questioning Its Benign Nature - Donna Erven; Tom J. G. Gevers; Bart Spaetgens; Renée A. G. Brüggemann (Clinical Case Reports)
ABSTRACT Esophagitis Dissecans Superficialis is a rare disease and may not be as benign as previously perceived, particularly in frail older patients, as illustrated in this case. Recognizing its potential severity early, especially in the presence of relevant comorbidities, is crucial for preventing negative health outcomes.